TANGGUNG JAWAB AUDITOR DAN APLIKASI STANDAR SAS 82 DALAM PENCEGAHAN & PENDETEKSIAN KECURANGAN PELAPORAN KEUANGAN - Rahmawati Rahmawati; Maylen Maylen; Annas Lalo; Mediyati Mediyati (AkMen JURNAL ILMIAH, 2015)
This paper discusses how the auditor's responsibilities, which set the standard for fraud detection financial statements of a company or government. Fraud is a phenomenon that a lot happens to intentionally manipulate financial statements with the aim tertenti, fraud becomes a problem and the responsibility of the auditor in mendetekdi fraud, in this paper presented several standards related to the auditor's responsibility standards, this paper is a review of previous articles related with fraud